Correction: Soares, D.J. Bridging a Century-Old Problem: The Pathophysiology and Molecular Mechanisms of HA Filler-Induced Vascular Occlusion (FIVO)—Implications for Therapeutic Interventions. Molecules 2022, 27, 5398 - Danny J. Soares (Molecules)
In the original publication [...]